Are students staying engaged in digital learning? a look at its benefits and challenges - Hashim, Hazwati (Universiti Teknologi MARA, Negeri Sembilan, 2025)
As technology continues to evolve, it has transformed the way education is delivered around the world. More universities, schools, and students are utilising online platforms, video lessons, and learning apps as part of their daily studies. Instead of sitting in a traditional classroom, many students now learn from home or other remote locations, using laptops, tablets, or even smartphones. This shift has made learning more flexible, allowing students to study at their own pace and access a wide range of resources with just a few clicks. However, while digital learning offers many new opportunities, it also raises an important question: are students truly engaged and motivated in this new way of learning, or are they struggling to stay focused behind the screen? Digital learning brings several advantages that make education more accessible and adaptable. Dhawan (2020) states that students can attend classes from any location, revisit recorded lessons and use digital tools that match their learning styles. Interactive features such as quizzes, videos, and educational games often make lessons more engaging and easier to understand.